The transition phase: preparing to launch a laboratory. Issue 10 (October 2022) - McKinley, Kara L.; Didychuk, Allison L.; Nicholas, Dequina A.; Termini, Christina M.
Abstract : The process of starting a laboratory varies between institutions. However, there are universal tasks all investigators will need to address when launching their laboratories. In this piece, we provide a brief summary of considerations for incoming group leaders to centralize this information for the scientific community.